(untitled) (Journal of actual problems of jurisprudence, 2018)
The article considers the collision of two legislations acts: the code of criminal procedure and the instruction of application of pledge and home arrest as preventive punishment, and also the cause of preventing the usage of pledge in criminal process of the Republic of Kazakhstan. Keywords: deposit, a measure of restraint, prosecuting agency, property.